An Analysis of the Socio-Economic Profile of Selected Students and the Cost of Degree Programs at the Philippine Normal University: Basis for Tuition Fee Policy Review - Ferrer, Jerick C.; Hermosisima, Maria Victoria C.; Abulencia, Arthur S. (ATIKAN, 2014)
ABSTRACT: The Philippine higher education sector is not immune to the fiscal pressure plaguing the entire public sector as a whole. So, finding other sources of funding is imperative for the survival of the State Universities and Colleges (SUCs) and for ensuring the delivery of quality education. The study sought to gather relevant data and other information that policy-makers and the management of PNU (Philippine Normal University) can utilize in examining the efficiency and sustainability of the existing tuition policy of the university. The study focused on the three important determinants of tuition fee rates: (1) the cost of degree programs being offered by PNU; (2) the ability to pay of its students; and (3) the effect of the inflation rate on the real value of the tuition fee rate of the university. Also, a comparative analysis of the tuition fee rates of other Higher Education Institutions (HEIs) in offering teacher education was done to compliment more insights to policy-makers and the management of the university. The findings are pointing to a need for the university to revisit its views and policy on the tuition fee and start the dialogue among its stakeholders addressing the issue.KEY WORD: Philippine higher education, socio-economic profile, cost estimation, tuition fee policy, cost-sharing, and dialogue with the stakeholders.IKHTISAR: âAnalisis Profil Sosial-Ekonomi Mahasiswa Terpilih dan Biaya Program Sarjana di Universitas Pendidikan Filipina: Dasar untuk Kajiulang Kebijakan Biaya Kuliahâ. Sektor pendidikan tinggi Filipina tidak kebal terhadap tekanan fiskal yang mengganggu seluruh sektor publik secara keseluruhan. Jadi, mencari sumber pendanaan lain sangat penting bagi kelangsungan hidup Perguruan Tinggi Negeri dan Sekolah Tinggi (PTN-ST) dan untuk memastikan pelayanan pendidikan yang berkualitas. Penelitian ini berusaha untuk mengumpulkan data yang relevan dan informasi lainnya, dimana para pembuat kebijakan dan pengelola PNU (Universitas Pendidikan Filipina) dapat memanfaatkan dalam memeriksa efisiensi dan keberlanjutan kebijakan pendidikan yang ada di universitas. Penelitian difokuskan pada tiga faktor penentu penting dalam tingkatan biaya kuliah: (1) biaya program sarjana yang ditawarkan oleh PNU; (2) kemampuan untuk membayar dari para mahasiswa; dan (3) pengaruh tingkat inflasi pada nilai riil dari tingkat biaya kuliah universitas. Juga, analisis komparatif tingkat biaya kuliah dari Perguruan Tinggi (PT) lainnya yang menawarkan pendidikan guru dilakukan untuk melengkapi wawasan yang lebih baik bagi pembuat kebijakan dan pengelola universitas. Temuan menunjukan perlunya universitas meninjau ulang pandangan dan kebijakan biaya kuliah, serta memulai dialog dengan para pemangku kepentingan untuk menangani masalah tersebut.KATA KUNCI: Pendidikan tinggi Filipina, profil sosial-ekonomi, estimasi biaya, kebijakan biaya kuliah, biaya-bersama, dan dialog dengan para pemangku kepentingan.Â Â Â Â About the Authors: Jerick C. Ferrer, Maria Victoria C. Hermosisima & Arthur S. Abulencia are the Lecturers at the Faculty of Social Sciences PNU (Philippine Normal University), Taft Avenue, Manila 1000, Philippines. Corresponding author is: arthurpnu@yahoo.comHow to cite this article? Ferrer, Jerick C., Maria Victoria C. Hermosisima & Arthur S. Abulencia. (2014). âAn Analysis of the Socio-Economic Profile of Selected Students and the Cost of Degree Programs at the Philippine Normal University: Basis for Tuition Fee Policy Reviewâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.4(2) December, pp.... Bandung, Indonesia: Minda Masagi Press, FKIP UNSUR Cianjur, and FPOK UPI Bandung, ISSN 2088-1290.Â Chronicle of the article: Accepted (August 4, 2014); Revised (October 9, 2014); and Published (December 27, 2014).